ANALISIS PENGARUH DISIPLIN KERJA, MOTIVASI DAN PEMBERIAN INSENTIF TERHADAP KINERJA PERAWAT RAWAT INAP (Studi pada Perawat Rawat Inap Rumah Sakit Jiwa Daerah Dr. Amino Gondhohutomo Kota Semarang) - Manasikana, Arina; Djastuti, Indi (Diponegoro Journal of Management, 2017)
The aim of this research was to recognize the influence of work discipline, motivationÂ  and incentives to the nurses performance background of the phenomena that occur in the nurses performance of Rumah Sakit Jiwa Daerah Dr. Amino Gondhohutomo Kota Semarang.This research use work discipline, motivation and incentives as the independenÂ  variable, while nurses performance as the dependen variable. This research was conducted at Rumah Sakit Jiwa Daerah Dr. Amino Gondhohutomo Kota Semarang, the data collection method was use quistionnaire technique that distributed into 125 nurses of Rumah Sakit Jiwa Daerah Dr. Amino Gondhohutomo Kota Semarang.Based on the multiple linear regression test, the result of this research showed that work discipline has positive and significant influence with the nurses performance. Motivation has positive and significant correlation with the nurses performance. Incentives has positive and significant influence with the nurses performance.